2011
DOI: 10.1002/lary.21856
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical characterization of human olfactory tissue

Abstract: Objectives/Hypothesis The pathophysiology underlying human olfactory disorders is poorly understood because biopsying the olfactory epithelium (OE) can be unrepresentative and extensive immunohistochemical analysis is lacking. Autopsy tissue enriches our grasp of normal and abnormal olfactory immunohistology and guides the sampling of the OE by biopsy. Furthermore, a comparison of the molecular phenotype of olfactory epithelial cells between rodents and humans will improve our ability to correlate human histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
158
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(172 citation statements)
references
References 33 publications
12
158
0
2
Order By: Relevance
“…1f). The CK18 immunostaining result was in accordance with the article of Holbrook et al [6]. The morphological and immunophenotypical features were consistent with the diagnosis of ONB, but with an aberrant expression of cytokeratins.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…1f). The CK18 immunostaining result was in accordance with the article of Holbrook et al [6]. The morphological and immunophenotypical features were consistent with the diagnosis of ONB, but with an aberrant expression of cytokeratins.…”
supporting
confidence: 89%
“…This latter being an important difference respect to Neuroendocrine Carcinoma (NEC) [1][2][3][4][5]. Furthermore another recent article by Holbrook et al [6] demonstrated that cytokeratin 18 (CK18) was positive in ONB separating tumor cells into nests.…”
mentioning
confidence: 99%
“…Nonetheless, our findings also have significant implications for the aging of the OE and olfactory dysfunction in the elderly. Despite the remarkable capacity for lifelong neurogenesis in the OE, we have previously demonstrated in both humans and mice that the aged OE has areas of aneuronal tissue, where the active GBC population has been exhausted and neurogenesis has ceased (67)(68)(69). However, the HBCs in this setting remain dormant and fail to regenerate the functional neuronal tissue, perhaps because Sus cells remain intact.…”
Section: Discussionmentioning
confidence: 98%
“…ASCL1 is essential for early development of neuronal progenitors in the olfactory epithelium and autonomic nervous system (12) . A few studies have investigated hASH1 in esthesioneuroblastoma (50,51,54) . In two of these studies, hASH1 transcripts were detected in 7 and 4 esthesioneuroblastoma tumors (50,51) ; in a third study, expression was seen by immunofluorescense staining (54) .…”
Section: Discussionmentioning
confidence: 99%